Sentidos e significados das mídias para alunos e professores de geografia: estudo dos aspectos didático-pedagógicos do uso das mídias nos municípios limítrofes de Nova Santa Rosa - PR / 2015-2016 - Heimerdinger, Camila (2016)
This work has reflections on the theme Media, part of the daily lives of people as technologies and serving speeches to "inform them. In contradiction there speeches distorted in favor of a group of people who need analysis (Speech Analysis) for your understanding. The objective is to analyze the schools of Núcleo Regional de Educação de Toledo-PR the Media for students and Geography teachers. Aims to understand the paradox of Media for students or students for the Media in different municipalities. The research presents the written definition and Media representation, where Geography teachers record photographs and students of the 3rd year of high school realize drawings that bring the senses and meanings to understand the term and its use. The search for sources in the methodology occurred with the use of questionnaires with open and closed questions in schools of the municipalities that border Nova Santa Rosa-PR. This is explained by the research to be the expansion of the Work Completion of Course TCC, accomplish with the respective municipality. As Result, the definitions of Media provide answers as a means of communication / information for students and teachers to fit into the school environment for educational use. The photos and drawings presented Media in daily life, such as handling, providing mechanical relationships, teaching in schools, politics, etc., in addition to the technology itself. Its use is private, teachers use a path and other students.